2008
DOI: 10.1016/j.bcp.2008.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 17α-hydroxyprogesterone caproate by hepatic and placental microsomes of human and baboons

Abstract: Recent data from our laboratory revealed the formation of an unknown metabolite of 17 hydroxyprogestrone caproate (17-HPC), used for treatment of preterm deliveries, during its perfusion across the dually perfused human placental lobule. Previously, we demonstrated that the drug is not hydrolyzed, neither in vivo nor in vitro, to progesterone and caproate. Therefore, the hypothesis for this investigation is that 17-HPC is actively metabolized by human and baboon (Papio cynocephalus) hepatic and placental micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
4
14
0
Order By: Relevance
“…Identity of the major metabolite (M2 HH ) generated from human hepatocytes needs to be elucidated, although preliminary data based on retention time and LC/MS data analysis indicate M2 HH (m/z ϭ 445) to be similar to M2 HLM . Similar results have recently been reported by Yan et al (2008). The study, performed in HLMs, reported the lack of 17-OHPC cleavage to release caproate ester based on radio-HPLC experiment.…”
Section: Expressed P450ssupporting
confidence: 89%
“…Identity of the major metabolite (M2 HH ) generated from human hepatocytes needs to be elucidated, although preliminary data based on retention time and LC/MS data analysis indicate M2 HH (m/z ϭ 445) to be similar to M2 HLM . Similar results have recently been reported by Yan et al (2008). The study, performed in HLMs, reported the lack of 17-OHPC cleavage to release caproate ester based on radio-HPLC experiment.…”
Section: Expressed P450ssupporting
confidence: 89%
“…It is administered as a weekly intramuscular injection of 250 mg. Because almost all lipidsoluble xenobiotics enter the fetal system through placental transfer, there is a high probability that 17-OHPC will penetrate through the placental barrier and gain access to the fetal circulation. Studies performed by using the dual perfused placental lobule technique have shown that 17-OHPC is transferred to the fetal circulation (Yan et al, 2008). Furthermore, analysis of fetal cord blood has shown significant 17-OHPC levels (S. Sharma, R. Venkataramanan, and S. C. Strom, unpublished data), thus confirming the transplacental transport from the mother to the fetus.…”
Section: Introductionmentioning
confidence: 83%
“…This procedure enabled partial elucidation of the 17-OHPC metabolite structure in adult and fetal hepatocytes and its comparison with previously reported data in adult liver microsomes (Yan et al, 2008).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The induction of CYP1A1 by maternal cigarette smoking or drug abuse and the effect of steroids has been amply demonstrated (Paakki et al 2000a;Paakki et al 2000b). Recently, metabolism of the progesterone, 17 hydroxyprogeteron caproate, (17-HPC) was studied on placental microsomes revealing that the extent of 17-HPC metabolism was much lower than that by the liver (Yan et al 2008).…”
Section: Placental Microsomesmentioning
confidence: 99%